Meneliti hubungan antara iklim motivasi dan tingkat kecemasan atlet bola tangan pra-kompetisi: Wawasan gender - Saniyah Nur’aini, Fenni; Fitri, Mustika; Hamidi, Ahmad; Apriady, Hilmy (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Coaches significantly influence athletes' needs and psychological performance by influencing the motivational climate in sports. The study aimed to analyze the relationship between the motivational climate of coaches and the anxiety of handball players before competitions, with a special emphasis on gender disparities in sports. The population in this study is the West Java National Sports Week Handball team, which totals 30 athletes. The sample in this study uses the total sampling method, so the sample in this study is 30. The data collection technique in this study uses the Perceived Motivational Climate in Sport Questionnaire-2 and the Competitive Sport Anxiety Inventory-2R questionnaire. The data analysis technique in this study uses a simple correlation test analysis using the product moment correlation formula and a quantitative descriptive methodology with the help of SPSS. These findings show that the level of anxiety and motivational atmosphere of coaches is significantly positively correlated in both male athletes (p-value 0.008) and female athletes (p-value 0.000). Based on descriptive statistical analysis, male athletes had a greater average level of anxiety (45.7550) than female athletes (40.5709). In contrast, female athletes were more influenced by the motivational climate (average score of 89.9769) than male athletes (84.3422). Based on the study's findings, gender has an impact on anxiety ahead of the competition, and male and female athletes react differently to pre-competition stress.